Eco-green mathematics and artificial intelligence: a systematic review on sustainable mathematical literacy - Sunismi; Abdul Halim Fathani; Yayan Eryk Setiawan; Gusti Firda Khairunnisa (Mandalika Mathematics and Educations Journal, 2025)
The advancement of eco-green mathematics and artificial intelligence (AI) in education provides opportunities to improve sustainable mathematical literacy and support innovative learning practices. This study aims to provide a comprehensive overview of research trends, roles, and best practices in the integration of AI and eco-green mathematics to strengthen sustainability-oriented mathematical literacy. This study uses the systematic literature review (SLR) method with strict guidelines, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A literature search was conducted through the Scopus database for articles published between 2019 and 2025, resulting in 34 studies relevant to this topic. The results show that AI in mathematics education is applied through intelligent tutoring systems, adaptive learning platforms, and machine learning-based tools, while eco-green mathematics emphasizes mathematical modeling to answer ecological and social sustainability challenges. Most of the research was conducted in Europe, Asia, and the United States, with a predominance of conceptual, bibliometric, and mixed-approach studies. The analysis highlights key themes such as trends and concepts, the role of AI, best practices, challenges and opportunities, and future research directions related to sustainable mathematical literacy. Therefore, the synergy of smart technology, green curriculum, and pedagogical innovation will be the key to building sustainable mathematical literacy in the digital era.